2000
DOI: 10.1097/00004872-200018100-00012
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment corrects vascular insulin resistance in hypertension

Abstract: These data show, for the first time, that long-term metformin treatment corrects vascular insulin resistance and improves endothelium-dependent vasorelaxation in hypertension. These effects appear to be secondary to metformin-induced improvements in metabolic derangements (versus a direct vascular action of metformin). Improving the vascular effects of insulin may serve to decrease peripheral tone, attenuate blood pressure and improve insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 7 publications
2
32
0
2
Order By: Relevance
“…Unlike traditionally used glucose-lowering reagents, such as sulfonylureas or insulin, metformin improves cardiovascular functions and reduces cardiovascular risks in diabetes (10 -15). Several studies both in vitro and in vivo have shown that metformin has insulin-sensitizing effects (13)(14)(15). Despite the long history and success of metformin as a treatment for type II diabetes, its mechanism of action remains an enigma.…”
mentioning
confidence: 99%
“…Unlike traditionally used glucose-lowering reagents, such as sulfonylureas or insulin, metformin improves cardiovascular functions and reduces cardiovascular risks in diabetes (10 -15). Several studies both in vitro and in vivo have shown that metformin has insulin-sensitizing effects (13)(14)(15). Despite the long history and success of metformin as a treatment for type II diabetes, its mechanism of action remains an enigma.…”
mentioning
confidence: 99%
“…Most animal models mimic end-stage type 2 diabetes (e.g., Zucker diabetic fatty and LA/N corpulent rats). However, chronic high-sugar diets produce whole body insulin resistance and hypertriglyceridemia without obesity or hyperglycemia (24,44), thereby mimicking the metabolic changes that precede the development of type 2 diabetes. We (10) have previously shown that treatment with metformin prevents both whole body insulin resistance and cardiomyocyte dysfunction, thus establishing an association between the two.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of insulin on NO production, we compared the cumulative dose response to PE (1 nmol/l to 10 mol/l) before and after a 2-h incubation with insulin (100 mU/ml Actrapid; Novo Nordisk) (22,23). This dose of insulin was found to be optimal in preliminary experiments.…”
Section: Methodsmentioning
confidence: 99%